E-books as a tool to improve reading comprehension among Year 4 primary ESL students - Nor Azmi, Nadhirah; Zahari, Zaleha (AJELP: Asian Journal of English Language and Pedagogy, 2024)
In Malaysian primary ESL classrooms, students have many different texts to read. Through reading, they acquire much of their knowledge and understanding of the different subject areas, and reading often forms the basis of follow-up work such as class discussions or homework questions. Through the researcher’s experiences and observations, many students have difficulties making sense of the reading texts that are too difficult for them. Students were struggling to comprehend the reading texts from the printed textbooks. Thus, this paper is written to investigate the effectiveness of using E-books to improve reading comprehension among ESL primary school students. Students’ perceptions of using E-books to improve reading comprehension are also further explored in this paper. The total of 50 students from Year 4 in one of the primary schools in Perak participated in this study. The participants were divided into the Control Group and the Experimental Group. They took the pre-test, and post-test to identify the differences of scores obtained after reading the short story and graphic novel. In addition, questionnaire was distributed to the 25 students from the Experimental Group after the test. This research found that there is a significant difference in scores between students who use printed books and E-books during reading sessions whereby students who use E-books score higher marks with a value (t (24) = -2.376, p = 0.026), p < 0.05. Despite the improvement shown after utilising E-books, more than half of the students stated that they are less interested to read using E-books than printed books. Nonetheless, teachers should understand the need to inculcate students with ICT knowledge is crucial in moving forward to the digitalization of education. This research will also help students to understand the benefits that E-books can give for them.